IMMU-51. PROFILING THE IMMUNE SYSTEM IN PRIMARY AND RECURRENT GLIOBLASTOMA. (11th November 2019) - Maddison, Kelsey; Graves, Moira; Bowden, Nikola; Vilain, Ricardo; Fay, Michael; Tooney, Paul
Abstract: Immunotherapy has been shown to have benefit in some solid tumours including melanoma where immune infiltration can be pronounced. Until recently the central nervous system was thought to be immune privileged. Whilst research has shown that immune cells are capable of infiltrating tumours from glioblastoma patients, to date immunotherapy trials have not consistently shown a benefit in these patients. The aim of this study was to profile the immune system in primary and recurrent tumours from glioblastoma patients. Formalin-fixed paraffin-embedded sections of primary and matched recurrent tumours from 13 patients with glioblastoma were processed for immunohistochemical labelling of a range of immune cell markers. Immune infiltration was scored on digitally scanned immunolabelled sections using a categorical system of 0 (absent), 1 (present), 2 (moderate) and 3 (marked). CD3+ cells were observed in three topographical locations within primary and recurrent glioblastoma tumours namely the tumour proper, perivascular spaces and associated with haemorrhages within the tumour. CD3+ cell infiltration into the tumour proper was present (Score = 1) in 7 of 13 primary and recurrent tumours. Only one case (case #9) had CD3+ infiltration scores > 1 for both primary (score = 3) and recurrent tumour (score = 2). CD3+ cells were observed in perivascular spaces in 10 of the 13 cases of primary and recurrent glioblastoma. Only case #9 had CD3+ cells in perivascular spaces that was scored >1 for both primary and recurrent tumours. In conclusion, whilst CD3+ infiltration was observed in the tumour proper and perivascular spaces within both primary and recurrent glioblastomas, the level of infiltration was quite low in this small cohort and as such requires further investigation in a larger cohort.